prove if an identity
csc (x)-cot (x)=sin (x)/1+cos(x)
2 answers
you just have to use () symbols so we know what you mean.
Assuming you mean
(csc (x)-cot (x))=sin (x)/(1+cos(x))
then
cscx-cotx = 1/sinx - cosx/sinx
= (1-cosx)/sinx
now, multiply top and bottom by 1+cosx and you get
(1-cosx)(1+cosx) / (sinx(1+cosx))
= (1-cos^2x)/ (sinx(1+cosx))
and it should be easy from here on.
(csc (x)-cot (x))=sin (x)/(1+cos(x))
then
cscx-cotx = 1/sinx - cosx/sinx
= (1-cosx)/sinx
now, multiply top and bottom by 1+cosx and you get
(1-cosx)(1+cosx) / (sinx(1+cosx))
= (1-cos^2x)/ (sinx(1+cosx))
and it should be easy from here on.